The Roots of The Problem of Islamic Education and Criticism of Modern Islam Post The Events of September 11, According to Ibrahim M. Abu Rabi - Anwar Sa'dullah; Muhammad Zainuddin; Muhammad Asrori (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2021)
The discourse on the problem of Islamic education and modern Islamic history is a problem that continues to be solved. On this basis, it is necessary to criticize and elaborate the root of the problem that makes the problem able to be resolved. Moreover, the study of Islamic education and the history of the problems in the midst of Muslims is very complex. Therefore, in this article, we try to look at and examine the root causes of Islamic education and how modern Islamic history after the events of 11 September 2001 at the World Trade Center Building which killed many people. This incident also made the world community perceive Islam as a religion of violence and teach terrorism. This is what is in the international area. Thus, Islam is frightening in the eyes of the international community. For this reason, an in-depth investigation and study is needed to reveal the background and impact of the post-September 11 tragedy. Finally, it also finds the root causes of modern Islamic history and the roots of the problems that lie within the contemporary Islamic education system.